The Relationship Between Nursing Agency and Self Care Behavior In Hypertensive Elderly - Sakti, Ifa Pannya; Luhung, Monika (Universitas Tribhuwana Tunggadewi, 2024)
Nurses as nursing agencies play a crucial role in efforts to control blood pressure, especially in elderly, through educational programs that promote self-care behavior and healthy lifestyle changes. The aim of this study is to analyze the relationship between nursing agencies and self-care behavior in elderly with hypertension in the Prolanis Group of Tajinan Health Center, Malang Regency. This research uses quantitative, retrospective and cohort design. The study population consist of all elderly suffering from hypertension who are members of the Prolanis group at Tajinan Community Health Center, Malang Regency, totaling 142 people. A purposive sampling technique was employed, with inclusion criteria of elderly people aged over 60, having suffered from hypertension for 1 year, receiving pharmacological therapy for hypertension from the Tajinan Community Health Center, regularly participating in Prolanis activities for the past 3 months, and demonstrating effective communication abilities. To assess the perception of nursing agency, the study uses the Patient Satisfaction with Nursing Care (PSNC) questionnaire. Self-care behavior assessment are measured using the Hypertension Self-Management Behavior Questionnaire (HMSBQ). The final sample was 60 elders, with data collection conducted between May and June 2024. Data analysis was performed using simple linear regression with SPSS. The results indicate a significant relationship between nursing agencies and self-care behavior in elderly with hypertension (p value = 0.000 0.05). The finding suggest that the role of nursing agencies is very influences on self-care behavior in elder with hypertension, indicating that elderly people have high level of trust in the health information provided by nurses.